Hypertext of Duysebek Nakipov. (Eurasian Journal of Philology Science and Education, 2015)
In the given paper the aesthetic, stylistic, especially poetological features of D. Nakipov (famous Kazakh poet and writer) are studied, the main features of the author’s discourse are also examined. They fit well within the parameters of postmodern literary techniques and style, for example: function codes and markers, symbolism, affectation syntax and quirky shapes, expressiveness and impressionism can be relegated. By analyzing the aesthetic component of the work, the characteristics of author discourse, conceptual characteristics and strategies of the author, there is the conclusion that the novel of D. Nakipov is a sample of postemodern hypertext literature in a new wave of Kazakhstan.
Keywords: hypertext; fractal; puzzle; culture-rheme; marker; post-modernism; author’s discourse